National immunization policies and practices for migrants in EU/EEA countries. (30th September 2020) - Marchetti, G; Giambi, C; Del Manso, M; Ranghiasci, A; Nacca, G; Dente, M G; Marceca, M; Adel Ali, K; Declich, S
Abstract: Background: Migrants represent a potential vulnerable group and adequate health protection, including vaccine preventable diseases prevention, should be ensured. The aim of this survey was to map national immunization policies and practices targeting asylum seekers, refugees and irregular migrants in EU/EEA countries. Methods: A web-based cross-sectional survey was conducted in 28 EU and 2 EEA countries within the ECDC funded Vaccine European New Integrated Collaboration Effort (VENICE) Project in the period January-April 2018. Results: All countries but one completed the survey and 28 countries offer vaccination to migrants. A national regulation/legal framework supporting migrant immunization is available in most countries. This is specifically established for migrants' health services for 5, part of the National Immunization Programme (NIP) for 15 and both for 3 countries. All the vaccinations included in the NIP appropriate for age are offered to children/adolescents in 27 countries and to adults in 13. In 15 countries offering only certain vaccinations to adults, priority is given to DT, MMR and polio. Vaccinations are mainly given at holding/community level and only 5 countries vaccinate at entry level. A vaccination card is delivered in 23/28 countries to children/adolescents and 24/28 to adults. Recording of individual data vary highly: for children/adolescents and adults, respectively, 15 and 12 countries use an electronic database, 5 and 4 use only paper registry, 2 and 3 use both electronic and paper registries, while 6 and 9 countries do not record information at all. Individual and aggregated data are not made available from the sites where vaccinations are delivered to other local or national institutions in 13 and 15 countries. Conclusions: Although policies about immunization of migrants are available in most of EU/EEA countries, there are important differences as to their objectives and implementation, especially methods of recording and transmitting data. Key messages: Given the survey results and the migrants' mobility, it is important to share data within and across countries to better respond to migrants' immunization needs. Strengthening partnerships between countries of origin, transit and destination, and sharing documentation may ensure the completion of vaccination series and avoid unnecessary revaccinations.